HUBUNGAN JUMLAH LEUKOSIT TOTAL DAN JUMLAH TROMBOSIT TERHADAP HASIL KEPOSITIFAN TUBEX-TF PADA PASIEN DEMAM TIFOID DI RSUD Dr. PIRNGAlDI KOTAl MEDAN TAHUN 2018-2021 - UTAMI, MEGA DIAHSYAH; IRMA, FANI ADE (JURNAL ILMIAH SIMANTEK, 2023)
Typhoid fever is an infection of the digestive tract caused by Salmonella typhi and Salmonella serovalr Palraltyphi (important causes of typhoid fever). Typhoid fever can be diagnosed based on clinical signs, symptoms, and laboratory tests. Leukopenia occurs due to the invasion of Sallmonellal Typhi Balcterial into halemopoetic organelles such as lymph nodes, tonsils, and the spleen of the spinal cord, thereby depressing the rate of hemopoiesis. Decreasing production of plaltelets in the bone malrrow can be caused by viral infections, malturaltion of plaltelet precursor cells in the bone malrrow, raldialtion, bone malrrow alplalsia, malignancy or cancer in the bone malrrow, and drugs that suppress blood cell production in the bone malrrow. This study used an observational alnallytic research method with a cross-sectional design. Daltal collection uses secondary daltal from medical records. The research sample of typhoid fever patients at RSUD Dr. Pirngaldi Medaln City in 2018–2021, which met the inclusion and exclusion criteria, was obtained with a total sample of 71 patients. Daltal alnallysis was performed univalrially and bivalrially using the chi squalre test. The result of this research is that there were 37 patients with Tubex-TF +4, 26 patients with Tubex-TF +6, and 8 patients with Tubex-TF +8. Leukocytes were detected in 9 patients, normal leukocytes in 58 patients, and abnormal leukocytes in 4 patients. Plaltelets were detected in 12 patients, normal plaltelets in 51 patients, and abnormal plaltelets in 8 patients. The conclusion is that there is a relationship between total leukocyte count and tubex-TF positive results in patients with typhoid fever. There is a relationship between plaque count and tubex-TF positive results in typhoid fever patients.